The Antigen Processing Pathway in B Cells Utilizes Peripheral Endocytic Recycling Compartments - Rajala, Johanna (My University, 2019)
B cells are responsible for the humoral responses of the adaptive immune system. B cells also act as antigen presenting cells: they internalize protein antigens and process them into peptides for presentation on Major Histocompability Complex class II -complexes for T cells. After this, B cells receive a stimulus back from T cells and get fully activated. In addition to antibody secreting cells, activated B cells differentiate into memory cells laying the base for the immunological memory. Despite the importance of B cell antigen processing for humoral immunity, the mechanisms of it still remain poorly understood. While characterizing the antigen processing pathways, we have found atypical vesicles not described in the literature. Thus, my thesis aimed at characterizing those vesicles and investigate their role in antigen processing in B cells. Here we show that antigen can be processed quickly in peripheral vesicles. Immunofluorescence staining and spinning disk confocal microscopy revealed the novel vesicles to resemble Endocytic Recycling Compartment, but distinct with the ability to degrade cargo. With different inhibitors and mutants of Rab- proteins we were able to prevent the classical/slow antigen processing pathway, however, by utilizing Enzyme Linked ImmunoSorbent Assay we show that treated B cells were still able to activate T cells. These findings pave the way for further investigation in antigen processing in B cells. Better understanding of antigen processing leads to better understanding of various immunodeficiencies and autoimmune disorders, and further, can contribute to the development of improved vaccine therapies.